Using an original triage and on call management tool aids identification and assessment of the acutely unwell surgical patient. Issue 2 (27th April 2018) - Hodge, Stacie; Helliar, Sebastian; Macdonald, Hamish Ian; Mackey, Paul
Abstract : Until now, there have been no published surgical triage tools. We have developed the first such tool with a tiered escalation policy, aiming to improve identification and management of critically unwell patients. The existing sheet which is used to track new referrals and admissions to the surgical assessment unit was reviewed. The sheet was updated and a traffic light triage tool generated using National Early Warning Scores (NEWS), sepsis criteria and user discretion. A tiered escalation policy to guide urgency of assessment was introduced and education sessions for all staff undertaken, to ensure understanding and compliance. Through multiple 'plan-do-study-act' cycles, the new system and its efficiency have been analysed. Prior to intervention, documentation of NEWS did not occur and only 13% of admission observations were communicated to the surgical team. Following multiple cycles and interventions, 93% of patients were fully triaged, and 80% of 'red' and 'amber' patients' observations were communicated to the surgical team. The average time for a registrar to review a 'red' patient was 37 min and 79% of 'green' patients were reviewed within an hour of their presentation. Rapid identification of the unwell patient is crucial. Here we publish the first triage tool that enables early assessment of septic and otherwise potentially unwell surgical patients.